2019
DOI: 10.1242/jcs.231993
|View full text |Cite
|
Sign up to set email alerts
|

Yap induces osteoblast differentiation by modulating Bmp signalling during zebrafish caudal fin regeneration

Abstract: Osteoblast differentiation is a key process for bone homeostasis and repair. Multiple signalling pathways have been associated with osteoblast differentiation, yet much remains unknown on how this process is regulated in vivo. Previous studies have proposed that the Hippo pathway transcriptional co-activators YAP and TAZ maintain progenitor stemness and inhibit terminal differentiation of osteoblasts, whereas others suggest they potentiate osteoblast differentiation and bone formation. Here, we use zebrafish c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…Hippo-YAP signaling pathway is also involved in osteoblast differentiation through multiple biological mechanisms. The suppression of YAP may induce lowering ligand bmp2a in MSCs, leading to a severe damage of Bmp signals in osteoblasts nearby, which downregulates osteoblast differentiation through a cell non-autonomous way (Brandão et al, 2019). In a recent vivo study it is demonstrated that suppression of OLFML1, a missense mutant gene in patients with congenital scoliosis, leads to the nuclear translocation of YAP thus promoting expression of target genes and results in an accelerated mineralization process of osteoblasts, suggesting OLFML1 inhibits bone development through a biomechanical mechanism dependent on Hippo-YAP signaling pathway in osteoblasts (Murakami et al, 2018).…”
Section: The Influence Of Hippo-yap Signaling On Osteogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Hippo-YAP signaling pathway is also involved in osteoblast differentiation through multiple biological mechanisms. The suppression of YAP may induce lowering ligand bmp2a in MSCs, leading to a severe damage of Bmp signals in osteoblasts nearby, which downregulates osteoblast differentiation through a cell non-autonomous way (Brandão et al, 2019). In a recent vivo study it is demonstrated that suppression of OLFML1, a missense mutant gene in patients with congenital scoliosis, leads to the nuclear translocation of YAP thus promoting expression of target genes and results in an accelerated mineralization process of osteoblasts, suggesting OLFML1 inhibits bone development through a biomechanical mechanism dependent on Hippo-YAP signaling pathway in osteoblasts (Murakami et al, 2018).…”
Section: The Influence Of Hippo-yap Signaling On Osteogenesismentioning
confidence: 99%
“…Last but not least, it's worth noticing that Hippo-YAP regulates cellular osteogenic function in not only cell autonomous mode but also non-autonomous mode (Brandão et al, 2019;Wang L. et al, 2020), which further contributes to the complexity of the working manner of Hippo-YAP pathway.…”
Section: Friend or Foe? The Discrepancy Around Hippo-yap Regulatory Ementioning
confidence: 99%
“…Fin amputation in zebrafish has allowed for in depth examination of the different mechanisms and cellular pathways. The study of Hippo pathway activators YAP and TAZ in fin during osteogenic regeneration demonstrated that YAP induces osteoblast differentiation through the modulation of Bmp signaling [ 41 ].…”
Section: Genes Involved In Bone Formation and Zebrafish Modelsmentioning
confidence: 99%
“…However, the different cell signaling effects promoted by Hippo pathway might vary in a context-dependent manner [ 64 ]. In this regard, a zebrafish regeneration model has been used to clarify Hippo pathway’s role in the differentiation and maturation of osteoblast lineage [ 41 ]. The authors, by using the zebrafish caudal fin regeneration model, addressed a new mechanism promoted by Hippo–Yap pathway, suggesting Yap involvement in the signaling cascade regulating osteoprogenitor maintenance and subsequent cell differentiation.…”
Section: Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation